Back to work : why we need smart government for a strong economy - Clinton, Bill, 1946- (New York : Alfred A. Knopf, 2011)
'I wrote this book because I love my country and I'm concerned about our future,' writes Bill Clinton.'As I often said when I first ran for President in 1992, America at its core is an idea, the idea that no matter who you are or where you're from, if you work hard and play by the rules, you'll have the freedom and opportunity to pursue your own dreams and leave your kids a country where they can chase theirs.'
President Bill Clinton gives us his views on the challenges facing the United States today and why government matters--presenting his ideas on resolving the mortgage crisis, job creation, financial responsibility and offering a plan to get us'back in the future business.'
Includes bibliographical references.
Keywords: Economic stabilization -- Government policy -- United States; United States -- Economic policy -- 2009-; United States -- Economic conditions -- 2009-; United States -- Politics and government -- 2009-